2007
DOI: 10.1038/nature05624
|View full text |Cite
|
Sign up to set email alerts
|

Strain-resolved community proteomics reveals recombining genomes of acidophilic bacteria

Abstract: Microbes comprise the majority of extant organisms, yet much remains to be learned about the nature and driving forces of microbial diversification. Our understanding of how microorganisms adapt and evolve can be advanced by genome-wide documentation of the patterns of genetic exchange, particularly if analyses target coexisting members of natural communities. Here we use community genomic data sets to identify, with strain specificity, expressed proteins from the dominant member of a genomically uncharacteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
290
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(293 citation statements)
references
References 26 publications
2
290
0
1
Order By: Relevance
“…To include this aspect of microbial interactions in global ecosystems biology, an integrated effort is needed to detect both the production of, and the response to, the plethora of small molecules that are produced by these organisms. Environmental metabolomics approaches, combined with metagenomic, meta-transcriptomic [58] and metaproteomic [59,60] data, should eventually allow the reconstruction of ecosystem-wide combined protein small-molecule networks, similar to those that have been achieved for single organisms (see Further information for a link to the STITCH chemical-protein interactions resource [61]). This approach could ultimately result in the molecular modelling of community multicellular behaviour types other than quorum sensing, such as dispersal, nutrient acquisition and biofilm formation [62].…”
Section: Cell-cell Signalling -Communication and Quorum Sensingmentioning
confidence: 99%
“…To include this aspect of microbial interactions in global ecosystems biology, an integrated effort is needed to detect both the production of, and the response to, the plethora of small molecules that are produced by these organisms. Environmental metabolomics approaches, combined with metagenomic, meta-transcriptomic [58] and metaproteomic [59,60] data, should eventually allow the reconstruction of ecosystem-wide combined protein small-molecule networks, similar to those that have been achieved for single organisms (see Further information for a link to the STITCH chemical-protein interactions resource [61]). This approach could ultimately result in the molecular modelling of community multicellular behaviour types other than quorum sensing, such as dispersal, nutrient acquisition and biofilm formation [62].…”
Section: Cell-cell Signalling -Communication and Quorum Sensingmentioning
confidence: 99%
“…Two archaea, the thermoacidophile Sulfolobus and the halophile Halorubrum, have similar, intermediate HRR. Homologous recombination has been detected in the bacteria Thermotoga (Nesbo et al, 2006) and Leptospirillum (Lo et al, 2007) and the archaeon Ferroplasma (Tyson et al, 2004;Eppley et al, 2007), but these findings were based on non-MLST methods and so could not be included here.…”
Section: Extremophilesmentioning
confidence: 99%
“…Consequently, in recent studies, bacterial communities have been characterized by proteomic approaches (Wilmes and Bond, 2006a). The investigated environmental samples showed an intermediate complexity and were analyzed either by a separation step using 2-DE (Wilmes and Bond, 2006b;Benndorf et al, 2007) or by shotgun approaches (Ram et al, 2005;Lo et al, 2007). These studies revealed significant details about the analyzed communities, especially the different proteins involved in functional aspects.…”
Section: Introductionmentioning
confidence: 99%